Photoelectrochemical Dopamine Sensor Based on Cu-Doped Bi2WO6 Micro-Flowers Sensitized Cobalt Tetraaminophthalocyanine Functionalized Graphene Oxide. Issue 15 (1st January 2019) - Peng, Jinyun; Zhuge, Wenfeng; Liu, Yuxia; Zhang, Cuizhong; Yang, Wei; Huang, Yingying
Abstract : This present study describes in detail the construction of a simple and inexpensive photoelectrochemical (PEC) sensor for the detection of dopamine (DA). The cobalt tetraaminophthalocyanine covalently linked graphene oxide compound (CoTAPc-GO) was synthesized successfully by covalently bonding cobalt tetraaminophthalocyanine (CoTAPc) with graphene oxide (GO). The composite of CoTAPc-GO and Cu-Doped Bi2 WO6 (Cu-Bi2 WO6 ) micro-flowers is obtained via ultrasonic treatment, and then the resulting composite was dropped onto an indium tin oxide (ITO) glass electrode to construct working electrode (CoTAPc-GO/Cu-Bi2 WO6 /ITO). Under visible light illumination with the chronoamperometry, the CoTAPc-GO/Cu-Bi2 WO6 composite material modified electrode exhibited excellent photocurrent response toward the catalytic of DA. The effects of a series of experimental conditions including coating amount, bias voltage, electrolyte, and pH value were studied. At the optimal conditions, the photocurrent response signals showed a good linear relationship with the DA concentrations in the two concentration ranges of 0.05–5.0 μmol L −1 and 5.0–250.0 μmol L −1, and the limit of detection was 7.2 nmol L −1 (S/N = 3). The real samples of clinical drugs exhibited high accuracy and recovery rates. The composite of CoTAPc-GO and Cu-Bi2 WO6 provides a new way to prepare high sensitivity and high selectivity photoelectrochemical (PEC) sensors.